Metal‐Free Selective and Diverse Synthesis of Three Distinct Sets of Isoindolinones from 2‐Alkynylbenzoic Acids and Amines. Issue 47 (17th November 2020) - Jia, Xiuwen; Li, Pinyi; Zhang, Xiaoning; Liu, Siyu; Shi, Xingzi; Ma, Wenbo; Dong, Hongbo; Lu, Yangbin; Ni, Hangcheng; Zhao, Fei
Abstract : The metal‐free selective and diverse synthesis of three distinct sets of isoindolinones from 2‐alkynylbenzoic acids and amines has been achieved in a reaction‐condition‐controlled manner. This method exhibits valuable advantageous features such as available starting materials, broad substrate scope, excellent selectivity, good to high yields, good functional group tolerance, simple operation, high bond‐forming efficiency, and step economy, thus providing a convenient and efficient access to a variety of heterocyclic compounds incorporating the bioactive isoindolinone motif. Abstract : The metal‐free selective and diverse synthesis of three distinct sets of isoindolinones from 2‐alkynylbenzoic acids and amines in a controlled manner is reported. This process features metal free, readily available starting materials, broad substrate scope, excellent selectivity, good to high yields, good functional group tolerance, simple operation, high bond‐forming efficiency, and step economy.